Cara Mengatasi Inflasi Untuk Meningkatkan Pertumbuhan Ekonomi di Indnesia Berdasarkan Perspektif Ekonomi Islam - Auliya Ahmad Suhardi; Khairina Tambunan (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Within the scope of macroeconomics, one of the benchmarks used to view and measure economic stability in a country is inflation. From an economic perspective, inflation is an event in which the usual (general) price level increases continuously. Inflation can cause unrest for the community if it occurs continuously (prolonged). This study aims to find out and understand how to overcome inflation with an Islamic economic perspective. This research is a qualitative research with literature study method. The literature method is a series of activities related to the method of collecting library data, by reading and taking notes, and managing research materials. The activity of collecting data by searching for and collecting various books, journals, and scientific articles containing the concepts under study, to be reviewed and produce conclusions. As for how to overcome inflation in the perspective of Islamic economics, namely by implementing fiscal policy, monetary policy and other policies.